Evaluating the effect of diffuse and point source nutrient transfers on water quality in the Kombolcha River Basin, an industrializing Ethiopian catchment. (6th August 2018) - Zinabu, Eskinder; Kelderman, Peter; van der Kwast, Johannes; Irvine, Kenneth
Abstract: Many catchments in sub‐Saharan Africa are subject to multiple pressures, and addressing only point sources from industry does not resolve more widespread diffuse pollution from sediment and nutrient loads. This paper reports on a preliminary study of nutrient transfers into rivers in two catchments in the industrializing city of Kombolcha, North Central Ethiopia. Sampling of rivers and industrial effluents was done over two sampling periods in the wet season of 2013 and 2014. Catchments boundaries and land use map were generated from remote sensing and ground data. Higher total nitrogen (TN) concentrations were found from sub‐catchments with largest agricultural land use, whereas highest total phosphorus (TP) was associated with sub‐catchments with hilly landscapes and forest lands. Emissions from brewery and meat processing were rich in nutrients (median TN: 21–44 mg L −1 ; TP: 20–58 mg L −1 ) but contributed on average only 10% (range 4–80%) of the TN and 13% (range 3–25%) of the TP loads. Nutrient concentrations in the rivers exceeded environmental quality standards for aquatic life protection, irrigation, and livestock water supply. In Ethiopia, more than 85% of farmers operate on less than 2 ha of land, with concomitant pressure for more intensive farming. Land is exclusively owned by the State, reducing a sense of land stewardship. As the City of Kombolcha moves to agricultural intensification and increased industrialization, attention is needed to fill gaps in monitoring of nutrient pollution in rivers and use information to reconcile development with land use and its degradation.